Farmers’ quality assessment of their crops and its impact on commercialization behavior: A field experiment in Ethiopia - Abate, Gashaw T.; Bernard, Tanguy (International Food Policy Research Institute, 2017)
Adoption of quality-enhancing technologies is often driven largely by farmers’ expected returns from these technologies. Without proper grades, standards, and certification systems, however, farmers may remain uncertain about the actual financial return associated with their quality-enhancing investments. This report summarizes the outcomes of a short video-based randomized training intervention on wheat quality measurement and collective marketing among 15,000 wheat farmers in Ethiopia. Our results suggest that the intervention led to significant changes in farmers’ commercialization behaviors—namely, it prompted farmers to adopt behaviors geared toward assessing their wheat’s quality using easily implementable test-weight measures, assessing the accuracy of the equipment used by buyers in their kebeles (scales, in particular), and contacting more than one buyer before concluding a sale. The training also led to improvements in share of output sold, price received, and collective marketing, albeit with important limitations. First, farmers who measured their wheat quality received a higher price, but only if their wheat was of higher quality. Second, farmers who found that their wheat was of higher quality were more reluctant to aggregate their wheat (that is, sell their products through local cooperatives) than those who found that their wheat was of lower quality. Lastly, the training intervention led to better use of fertilizer in the following season. Our discovery that a short training intervention can significantly change farmers’ marketing and production behavior should encourage the development of further interventions aimed at enhancing farmers’ adoption of improved technologies and commercialization.